Investigation of Integrated Organic Rankine Cycles and Wind Turbines for Micro-Scale Applications. (August 2018) - Morrone, P.; Algieri, A.; Castiglione, T.; Perrone, D.; Bova, S.
Abstract: The aim of this work is the investigation of the performance of an innovative biomass/wind energy integrated system for Combined Heat and Power (CHP) generation in small-scale applications. The system is based on an Organic Rankine Cycle (ORC) fed with biomass and a wind turbine (WT). The ORC and WT sub-systems operate in parallel to produce the required electrical energy and an auxiliary boiler provides thermal energy if the CHP output is low. A preliminary investigation is performed to define the proper size of the wind turbine. Afterwards, the analysis is focused on the integrated system. In particular, the application to the Italian residential sector is analysed. Results illustrate that hybridisation improves the global conversion efficiency, by reducing the biomass consumption and overcoming the intermittency of the wind source. When the wind source is significant, the ORC system can be switched off or operated at partial load.